2011
DOI: 10.1200/jco.2010.30.3909
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Patient-Provider Communication With the Electronic Self-Report Assessment for Cancer: A Randomized Trial

Abstract: Purpose Although patient-reported cancer symptoms and quality-of-life issues (SQLIs) have been promoted as essential to a comprehensive assessment, efficient and efficacious methods have not been widely tested in clinical settings. The purpose of this trial was to determine the effect of the Electronic Self-Report Assessment–Cancer (ESRA-C) on the likelihood of SQLIs discussed between clinicians and patients with cancer in ambulatory clinic visits. Secondary objectives included comparison of visit duration bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
301
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(321 citation statements)
references
References 16 publications
11
301
2
1
Order By: Relevance
“…9,[18][19][20][21] Multiple studies confirm that clinical integration of PROs does not increase the duration of clinic visits, that provider and patient satisfaction is high, and that all parties feel their use improves communication. 12,19,20,[22][23][24] The successful use of PROs in outpatient orthopedic surgery clinics highlights the feasibility of use in busy outpatient settings and the benefit in clinical decision making. Orthopedic clinics have integrated PRO collection into clinical practice to monitor patient pain, mobility, and function.…”
Section: Pro Use In Clinical Practice Is Feasible and Beneficialmentioning
confidence: 99%
See 1 more Smart Citation
“…9,[18][19][20][21] Multiple studies confirm that clinical integration of PROs does not increase the duration of clinic visits, that provider and patient satisfaction is high, and that all parties feel their use improves communication. 12,19,20,[22][23][24] The successful use of PROs in outpatient orthopedic surgery clinics highlights the feasibility of use in busy outpatient settings and the benefit in clinical decision making. Orthopedic clinics have integrated PRO collection into clinical practice to monitor patient pain, mobility, and function.…”
Section: Pro Use In Clinical Practice Is Feasible and Beneficialmentioning
confidence: 99%
“…Salient issues related to PROs, such as psychosocial issues and symptoms were more likely to be discussed for visits where the clinical team received the summary. 12,19,20 Some patients experienced better functioning as a result of the intervention. 12 Similar work in children with advanced cancer and pediatric cancer survivors has demonstrated that providing PRO data to clinicians increased discussion of psychosocial issues and improved the patient's health status in certain subpopulations (see Example 1).…”
Section: Pro Use Improves Physician Patient Communicationmentioning
confidence: 99%
“…In the study most of the nurses and allied health professions found the ESAS to enhance patient care, help patients to articulate their symptom issues, and facilitate follow-up with patients with past symptom issues. Similarly, in a study of an electronic version of ESAS, clinicians reported it as useful [35]. Some of the nurses noted, however, that even though they knew the advantages and possibilities that Choice could bring, they still did not have "good experiences" using it.…”
Section: Relative Advantagementioning
confidence: 99%
“…In terms of the theories under test, Berry et al 354 suggest that, in these instances, the Electronic Self-Report Assessment of Cancer report may have acted as an 'ice-breaker', giving patients or clinicians 'permission' to discuss sensitive issues. However, relative to the number of times it was reported at threshold, the number of times sexual function was actually discussed in the consultation, even in the intervention group, was relatively very small.…”
mentioning
confidence: 99%